Outcomes in 125 Individuals with Adrenal Incidentalomas from a Single Centre. A Retrospective Assessment of the 1 mg Overnight and Low Dose Dexamethasone Suppression Tests - Theodoraki, A.; Khoo, B.; Hamda, A.; Schwappach, A.; Perera, S.; Vanderpump, M.P. J.; Bouloux, P. M. (Hormone and Metabolic Research, 2011)
Adrenal masses discovered incidentally during imaging studies – adrenal incidentalomas (AIs) – are common and prompt investigations to exclude secretory lesions and malignancy. Their best management strategy is unknown. Our objectives were to identify all outcomes of AI investigation in a UK centre and to assess the performance of the 2 mg low dose (LDDST) and 1 mg overnight dexamethasone (ODST) suppression tests in this setting. Out of 125 patients referred to our centre between 2005 and 2009 with AIs, 16 (12.8%) were diagnosed with secretory adrenal adenomas. 24 patients (23%) failed to suppress on LDDST or ODST using a serum cortisol cut-off of 50 nmol/l for both tests; in 12 this was due to false positive results. 5 patients were diagnosed with adrenal Cushing’s syndrome and 7 with subclinical hypercortisolism. The use of a higher post LDDST (83 nmol/l) or ODST (138 nmol/l) cortisol cut-off would have resulted in missing 1 patient with Cushing’s syndrome and 4 with subclinical hypercortisolism or 2 patients with Cushing’s syndrome and 1 with subclinical hypercortisolism, respectively. In patients who had both tests, the ODST systematically resulted in higher post-test cortisol values compared with the LDDST. The adenoma diameter correlated with and was predictive of the post LDDST cortisol. Our results indicate that altering the post dexamethasone cut-off in accordance to published guidelines changes the performance of the suppression tests. The ODST may result in higher post-test cortisol levels compared to LDDST when used in patients with AIs.
Keywords: adrenal adenoma; Cushing’s syndrome; hypercortisolism